2020
DOI: 10.3390/ijerph17041194
|View full text |Cite
|
Sign up to set email alerts
|

Association of Urinary Levels of Bisphenols A, F, and S with Endometriosis Risk: Preliminary Results of the EndEA Study

Abstract: Aim: The aim of this study was to explore associations of urinary concentrations of bisphenols A (BPA), S (BPS), and F (BPF) and of thiobarbituric acid reactive substances (TBARS) with the risk of endometriosis in women of childbearing age. Methods: This case–control study enrolled 124 women between January 2018 and July 2019: 35 women with endometriosis (cases) and 89 women without endometriosis undergoing abdominal surgery for other reasons (controls). Endometriosis was diagnosed (cases) or ruled out (contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 51 publications
(65 reference statements)
0
23
0
1
Order By: Relevance
“…In the class of alkylphenols, octylphenol and nonylphenol are also represented. Bisphenol F and S have recently been used as substitutes for BPA, whose deleterious effects on health are starting to be known [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the class of alkylphenols, octylphenol and nonylphenol are also represented. Bisphenol F and S have recently been used as substitutes for BPA, whose deleterious effects on health are starting to be known [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“… Bias assessment within articles [ 10 , 11 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. …”
Section: Figureunclassified
“…Due to the suspected increase in the number of cases in the last decades [107], it is suspected that, in addition to the increased awareness among doctors and patients, environmental risk factors are suspected to also contribute to the onset and progression of this disease. This environmental hypothesis of the origin of the disease is also reinforced due to the estrogen-dependent nature of this pathology [53,108].…”
Section: Associations Between Pcp-and Cosmetic-released Edcs and Endometriosismentioning
confidence: 98%
“…Although the underlying mechanisms are still poorly understood, it has been suggested that, at least in part, EDCs might induce oxidative stress via estrogen receptor-α signaling pathways [52]. Moreover, EDC exposure has also been evidenced to trigger an inflammatory microenvironment [50,53]. With an intimate relationship, both oxidative and inflammatory responses have also been suggested as crucial mechanisms beyond a variety of chronic diseases, as well as some gynecological conditions such as endometriosis [54,55].…”
Section: Mechanisms Of Action Of Edcsmentioning
confidence: 99%
“…Furthermore, increasing evidence from both in vitro and animal studies suggest that BPA exposure, even at low doses, may have carcinogenic effects on breast cancer [ 48 ]. Moreover, BPA appears to increase the risk of endometriosis which, in turn, increases the risk of both coronary heart disease and ovarian cancer [ 49 , 50 ]. Finally, BPA exposure may induce endometrial stromal cell invasion and has a positive association with peritoneal endometriosis [ 51 ].…”
Section: Bpa and Comorbidities Predisposing To Severe Covid-19mentioning
confidence: 99%